Teachers' perception of the relationship between the characters of role players in schools and the level of culture of teaching and learning - Ghani, M.F.A.; Pourrajab, M. (2014)
The aim of this paper is to investigate the relationship between the characters of role players and level of Culture of Teaching and Learning (COTL) in schools. Additionally, the paper aims to identify the level of COTL is schools based on teachers’ perception. Data were collected from 280 teachers in secondary schools in Lorestan Province, Iran. To achieve these aims, the researchers conducted a research survey to determine the level of COTL, and applied multivariate regression analysis to investigate the relationship between the characters of role players and COTL. The findings of this study showed that, the level of COTL is high and also there is a positive and moderate relationship between the characters of principals, teachers, students, and parents and COTL. The teachers in this study pointed out that the character of students had a more important role for COTL. The study identifies some useful point for teaches to be more effective on the level of COTL.